Culinary reactions : the everyday chemistry of cooking - Field, Simon (Simon Quellen) (Chicago Review Press, 2012)
When you're cooking, you're a chemist! Every time you follow or modify a recipe you are experimenting with acids and bases, emulsions and suspensions, gels and foams. In your kitchen you denature proteins, crystallize compounds, react enzymes with substrates, and nurture desired microbial life while suppressing harmful microbes. And unlike in a laboratory, you can eat your experiments to verify your hypotheses. In Culinary Reactions, author Simon Field explores the chemistry behind the recipes you follow every day.